2011
DOI: 10.1017/s1743921312004759
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic clouds along the solar cycle: expansion and magnetic helicity

Abstract: Abstract. Magnetic clouds (MCs) are objects of extreme importance in the heliosphere. They have a major role on releasing magnetic helicity from the Sun (with crucial consequences on the solar dynamo), they are the hugest transient object in the interplanetary medium, and the main actors for the Sun-Earth coupling. The comparison between models and observations is beginning to clarify several open questions on MCs, such as their internal magnetic configuration and their interaction with the ambient solar wind.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The 73 month averages discussed earlier are mostly due to the difference in the maximum phases of the two cycles; cycle-24 rise phase is much weaker than the cycle-23 one (by 54%). Many of these quantities show solar cycle variation, confirming Dasso et al [2012] and Lepping et al [2015] when similar parameters are considered. The parameters (V L , B t , P t , VB z , and B z ) that are directly linked to the solar source show clear solar cycle variation, except for the large modulation caused by periods of extreme activity in the decay phase of cycle 23, viz., October-November 2003 Halloween eruptions [Gopalswamy et al, 2005a] and November 2004 eruptions [Gopalswamy et al, 2006;Echer et al, 2010].…”
Section: Solar Cycle Variationsupporting
confidence: 52%
See 1 more Smart Citation
“…The 73 month averages discussed earlier are mostly due to the difference in the maximum phases of the two cycles; cycle-24 rise phase is much weaker than the cycle-23 one (by 54%). Many of these quantities show solar cycle variation, confirming Dasso et al [2012] and Lepping et al [2015] when similar parameters are considered. The parameters (V L , B t , P t , VB z , and B z ) that are directly linked to the solar source show clear solar cycle variation, except for the large modulation caused by periods of extreme activity in the decay phase of cycle 23, viz., October-November 2003 Halloween eruptions [Gopalswamy et al, 2005a] and November 2004 eruptions [Gopalswamy et al, 2006;Echer et al, 2010].…”
Section: Solar Cycle Variationsupporting
confidence: 52%
“…We also investigate intracycle variations at a slightly finer scale by considering the annual averages of the MC parameters, somewhat similar to Dasso et al . [] and Lepping et al . [], although these authors consider different sets of parameters with some overlap with our parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The rise phase of cycle 24 was already interesting because the Sun emerged from a deep solar minimum that gained particular interest among solar-terrestrial scientists (Selhorst et al 2011;Tsurutani et al 2011a;Dasso et al 2012;Gopalswamy et al 2012a;Solomon et al 2013;Lean et al 2014;Potgieter et al 2014). Solar activity is typically represented by the international sunspot number (SSN), but there are many other measures, which are needed for a complete understanding of the solar variability.…”
Section: Methodsmentioning
confidence: 99%
“…Evidences collected over the years show that the solar cycle affects the occurrence of CMEs (e.g., Gopalswamy et al, 2003), with more CMEs during the active period and therefore an expected higher number of detected ICMEs. Previous studies have analyzed the dependence of specific properties of ICMEs and MCs (e.g., size, bulk velocity, or expansion) with the phase of the solar cycle (e.g., Dasso et al, 2012; Jian et al, 2011; Lepping et al, 2011). Furthermore, Hundhausen (1999) found that CMEs emitted during the active period tend to be faster than the ones emitted during the quiet period.…”
Section: Superposed Epochs Of Different Icme Groupsmentioning
confidence: 99%